2016
DOI: 10.1111/cas.12967
|View full text |Cite
|
Sign up to set email alerts
|

CD44 variant‐dependent redox status regulation in liver fluke‐associated cholangiocarcinoma: A target for cholangiocarcinoma treatment

Abstract: Expression of CD44, especially the variant isoforms (CD44v) of this major cancer stem cell marker, contributes to reactive oxygen species (ROS) defense through stabilizing xCT (a cystine–glutamate transporter) and promoting glutathione synthesis. This enhances cancer development and increases chemotherapy resistance. We investigate the role of CD44v in the regulation of the ROS defense system in cholangiocarcinoma (CCA). Immunohistochemical staining of CD44v and p38MAPK (a major ROS target) expression in Opist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 46 publications
1
58
1
Order By: Relevance
“…To test this, we examined the sub-G1 population by flow cytometry in MDA-MB-231 and HCT116 cells after treatment with vorinostat and/or SASP for 144 h. Vorinostat induced marked cell death in both cell lines when cotreated with SASP at 500 µM ( Figure 4A), which was close or below to IC50 values in MDA-MB-231 and HCT116 cells (Supplementary Figure S1B). inflammatory bowel disease and rheumatoid arthritis, has been considered to be repurposed as a promising antitumor drug [24][25][26][27][28][29][30][31][32].…”
Section: Sasp Increases Sensitivity To Vorinostat By Reducing Intracementioning
confidence: 99%
“…To test this, we examined the sub-G1 population by flow cytometry in MDA-MB-231 and HCT116 cells after treatment with vorinostat and/or SASP for 144 h. Vorinostat induced marked cell death in both cell lines when cotreated with SASP at 500 µM ( Figure 4A), which was close or below to IC50 values in MDA-MB-231 and HCT116 cells (Supplementary Figure S1B). inflammatory bowel disease and rheumatoid arthritis, has been considered to be repurposed as a promising antitumor drug [24][25][26][27][28][29][30][31][32].…”
Section: Sasp Increases Sensitivity To Vorinostat By Reducing Intracementioning
confidence: 99%
“…13 Sulfasalazine is an inhibitor of xCT-mediated cystine transporters 14 and exerts inhibitory effects against tumor growth, invasion, and metastasis in many types of cancers. 4,[15][16][17][18][19] Furthermore, previous studies reported that SSZ enhanced the effects of CDDP therapy. 20,21 However, limited information is currently available on the functional role of SSZ, which could modulate the CD44v9-xCT system in order to enhance CDDP-induced cytotoxicity and inhibit the metastatic potential of BC.…”
Section: Introductionmentioning
confidence: 97%
“…We focused on SSZ, an anti‐inflammatory drug approved for the treatment of inflammatory bowel disease and rheumatoid arthritis . Sulfasalazine is an inhibitor of xCT‐mediated cystine transporters and exerts inhibitory effects against tumor growth, invasion, and metastasis in many types of cancers . Furthermore, previous studies reported that SSZ enhanced the effects of CDDP therapy .…”
Section: Introductionmentioning
confidence: 99%
“…However, even if investigation of PLC metabolism is still at its very beginning in comparison with other tumor systems, recent evidence has revealed the importance of the metabolic rearrangement in PLC CSCs. CD44+ CCA CSCs adapt their redox status regulation according to their needs and contribute to reactive oxygen species (ROS) defense promoting glutathione synthesis by way of xCT (a cysteine-glutamate transporter), resulting in evasion of cell death [142] . Moreover, CD133+ HCC CSCs are characterized by high glycolytic metabolism with concomitant overexpression of glycolytic genes and enhanced extracellular acidification rate, demonstrating that CD133+ cells are more glycolytic compared to CD133-cells.…”
Section: Metabolic Reprogrammingmentioning
confidence: 99%